Burden of alcohol and other substance use and correlates among undergraduate students at Busitema University in rural Eastern Uganda after COVID-19 lockdown - Kirabira, Joseph; Kagoya, Enid Kawala; Mpagi, Joseph; Atala, Christine Etoko; Ndamanywa, Kalisiti; Okibure, Ambrose; Kibuuka, Ronald; Katongole, Fauz; Wandabwa, Julius (Nature Publishing Group, 2024)
Abstract Use of alcohol and other substances remains a major health concern among higher learning institutions. This study aimed at assessing the prevalence of alcohol and other substance use among students at Busitema University in Eastern Uganda. A cross sectional survey was conducted among 658 undergraduate students using a questionnaire consisting of Alcohol, Smoking and Substance Involvement Screening Tool and participant sociodemographic and clinical factors. Logistic regression was used to explore the associations. Two hundred sixty-five (40.3%) students reported ever using alcohol and 158 (24.0%) had used in last 3 months. Seventy-four (11.2%) students reported ever use of other substances including tobacco, cannabis, cocaine, stimulants sedatives and hallucinogens and 36 (5.5%) had used within the recent 3 months. After controlling for potential confounders, recent alcohol use was associated with engaging in romantic relationship (odd ratio (OR) = 1.9, P value (P) = 0.045) while having chronic medical conditions was protective (OR = 0.3, P = 0.031). On the other hand, recent use of other substances was 7 times higher among males (OR = 7.0, P = 0.008) compared to females while fourth year of study was protective (OR = 0.05, P = 0.011). Although alcohol use is a worsening challenge among university students, use of other substances is also highly prevalent after COVID-19 lockdown. There is need for universities to identify students with above factors and design interventions to address them in order to prevent the likely undesirable outcomes of alcohol and substance use.
Keywords: Alcohol, Substance use, University, Students, Uganda